Effects of Pediococcus pentosaceus on fermentation, aerobic stability and microbial communities during ensiling and aerobic spoilage of total mixed ration silage containing alfalfa (Medicago sativa L.). (18th February 2020) - Jiang, Di; Li, Bingnan; Zheng, Mingli; Niu, Dongze; Zuo, Sasa; Xu, Chuncheng
Abstract: The objective of this study was to evaluate the effect of Pediococcus pentosaceus inoculation on the fermentation quality and the dynamics of microbial communities during ensiling and aerobic exposure in total mixed ration (TMR) silage. The TMR were prepared using alfalfa ( Medicago sativa L.), maize meal, soybean curd residue, soybean meal, calcium carbonate, vitamin‐mineral supplement and salt (60.0:21.4:15.0:2.0:1.0:0.5:0.1, dry matter basis) with or without P. pentosaceus inoculation (10 5 cfu/g fresh matter) followed by 14 or 28 days of ensiling and exposed to air. Microbial communities were detected by high‐throughput sequencing. After ensiling, P. pentosaceus inoculation benefited silage fermentation as indicated by increased lactic acid content and decreased pH, whereas had no effect on aerobic stability. Taxonomic bacterial community was dominated by Lactobacillales after ensiling, with a notable increase in spoilage microorganisms as a result of aerobic exposure. Aerobically exposed TMR was characterized by an increase of operational taxonomic units belonging to the Hypocreales and with yeast genus Cryptococcus, whereas Monascus was the major mold genus in the aerobically exposed silages. Candida was detected with higher relative abundance only in 28 days aerobically exposed sample inoculated with P. pentosaceus . P. pentosaceus inoculation has good effects on improving the fermentation quality and shows a potential to inhibit the proliferation of Monascus at 28 days of ensiling.